The Assessment of Fatigue and its Related Factors in Patients with Cancer - Moloud Sharifi Rizi; Atefeh Ghanbari khanghah; Masoumeh Adib; Ehsan Kazem Nejad Leili (Guilan University of Medical Sciences, 2017)
Abstract Introduction: Cancer is a major health issue in Iran and in the rest of the world. Fatigue is one of the most complex and the most prevalent cancer-related problems that can affect various aspects of life for cancer patients. It can cause numerous problems. Objective: The aim of this study was to determine the level of fatigue and its associated factors in patients with cancer. Materials and Methods: In this descriptive-analytical study, 90 cancer patients referred to the oncology department in one of the teaching hospitals were assessed. The data collection tool was a questionnaire based on demographic information and the fatigue severity scale (FSS). This questionnaire consisted of nine questions with a numeric scale for answers ranging from 0 to 7. A score of 7 indicates the highest level of fatigue and 1 indicates no fatigue. The patients with above-average scores were considered to have fatigue and those with lower scores were considered to have no fatigue. To analyse the data, descriptive and inferential statistics (chi-square test, one-way ANOVA, and logistic regression) were used. Results: The mean age of the patients was 52.1 ± 14.4 years. The majority of the subjects were women (58.9%), married (91.1%), and with an educational level below diploma (40%). The average score of fatigue was 5.8 ± 0.54 out of 7. The results of the logistic regression model showed that the factors influencing cancer-related fatigue were the variable of unemployment (p =0.034, β= 1.1) and haemoglobin levels (p=0.049, β= 0.33). Conclusion: The results showed that in addition to providing physical care and nursing interventions, it is important to consider demographic factors and psychological interventions for the comprehensive management of problems in cancer patients, particularly fatigue.